2005
DOI: 10.1084/jem.20042066
|View full text |Cite
|
Sign up to set email alerts
|

MSH2–MSH6 stimulates DNA polymerase η, suggesting a role for A:T mutations in antibody genes

Abstract: Activation-induced cytidine deaminase deaminates cytosine to uracil (dU) in DNA, which leads to mutations at C:G basepairs in immunoglobulin genes during somatic hypermutation. The mechanism that generates mutations at A:T basepairs, however, remains unclear. It appears to require the MSH2–MSH6 mismatch repair heterodimer and DNA polymerase (pol) η, as mutations of A:T are decreased in mice and humans lacking these proteins. Here, we demonstrate that these proteins interact physically and functionally. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 62 publications
7
161
0
Order By: Relevance
“…The increasing reductions of A,T mutations are slightly parallel with increasing proportions of known hotspots of the error-prone polymerase (WA, and its inverse TW) (34). This may suggest that pol is not the major polymerase interacting with MMR in SHM in the absence of Ung, although it has been reported that pol can interact with Msh2/Msh6 (35).…”
Section: Discussionmentioning
confidence: 76%
“…The increasing reductions of A,T mutations are slightly parallel with increasing proportions of known hotspots of the error-prone polymerase (WA, and its inverse TW) (34). This may suggest that pol is not the major polymerase interacting with MMR in SHM in the absence of Ung, although it has been reported that pol can interact with Msh2/Msh6 (35).…”
Section: Discussionmentioning
confidence: 76%
“…The dA/dT-biased mutations in the transfected V H 1-DXP′ 1-J H 5 DNA suggest that Msh2, recruited by specific but yet identified features of V H 1-DXP′1-J H 5, triggers MMR in Phase 2. Translesion DNA polymerases, pol η in particular, would be recruited by Msh2 to insert mismatches mostly at dA/dT Indeed, pol η physically interacts with Msh2 (Wilson et al, 2005) and displays a preference in inserting transition at dA/dT (Rogozin et al, 2001;Zeng et al, 2001;Delbos et al, 2005;Martomo et al, 2005), consistent with the predominant dA/dT transitions in the V H 1-DXP′ 1-J H 5 DNA. In turn, the newly generated mismatches at dA/dT could trigger additional rounds of MMR, thereby introducing more mutations at dA/dT residues.…”
Section: Discussionmentioning
confidence: 91%
“…Second, U could be removed by uracil DNA glycosylase (UNG) to produce an abasic site, which when copied by low-fidelity DNA polymerases, would generate C:G transitions and transversions. Third, U could be recognized as a U:G mismatch by the MSH2-MSH6 mismatch repair (MMR) proteins, which would generate a gap that could be filled in by the low-fidelity DNA polymerase (pol) h to produce mutations of A:T base pairs (bp; Zeng et al 2001;Wilson et al 2005). The last two steps are also associated with strand breaks, which produce substrates for recombination during heavy-chain class switching.…”
Section: Aberrant Dna Repair Generates Antibody Diversitymentioning
confidence: 99%